Construção e estudo das condições de operação de uma unidade de pirólise para pneumáticos inservíveis - Partata, Andréia Ramos (2007)
Today the used tire is considered a residue with quite inadequate final disposition as in embankments. It can cause many environmental and human health problems because it can absorb gases and to burst. When it is burned into nature it forms toxicant substances as sulfur dioxide and powder material. An alternative use of the used is as energy source in industries that demand high amount of energy in your processes because its calorific value is of approximately 33 MJ/kg. This value is high when compared with the vegetable coal calorific value. In that sense, quicklime industry can take advantage of this low cost energy source and to receive this residue. The costs with fuel in this type of industry reach up to 50% of the final cost of the lime because they operate in very high temperatures. The pyrolysis of the used tires is a way to produce high calorific value fuels from used tires with no residue generation. In this way we can give a final destination to the used tires environmentally safe. The aim of this work was to design and to build an experimental unit of pyrolysis of the used tires and to investigate the possibility to use their products as industrial fuel. Besides, we intend to study the effect of the process variables such as temperature and pressure in the process yield and in the quality of the obtained products. Some analyses of the obtained products (pyrolytic coal and oil) were made in order to compare them with traditional fuels used in quicklime industries (vegetable coal and petroleum coke). The experimental results showed that when the temperature of the pyrolyser increases the percentage of pyrolytic coal decreases. These values varied from 35.18% to 41.35%. It was also observed that the yield of the pyrolytic oil is more dependent on pyrolyser temperature than the yield of the pyrolytic coal. We get a maximum yield of the pyrolytic oil of the 45.1% when the pyrolyser was operated in 500oC. In addition, it was verified that the pyrolytic oil can be used as liquid fuel due to its very high calorific value (from 40 to 42 MJ/kg), its low viscosity (from 1.6 to 3.7 cP) and its low sulfur content (from 0.97 to 1.54%).